Individual Behavior and Transformational Leadership on Innovative Work Behavior and Employee Performance - Situmorang, Gloria Rochelly; Riadi, Sukisno S.; Achmad, Gusti Noorlitaria (International Journal Labs, 2023)
This research aims to analyze the influence of individual behavior and transformational leadership on innovative work behavior and employee performance at PT Astra International Tbk - HSO Kaltim2. This study uses a quantitative approach and utilized a sample of 128 informants, representing 100% of the total permanent employee population at PT Astra International Tbk - HSO Kaltim 2. The author used SmartPLS version 3.2.9 as the analysis tool and conducted data analysis using PLS in two stages: first, by evaluating the outer model or measurement model, and second, by assessing the inner model or structural model. The results of the research showed that individual behavior had a positive and significant impact on innovative work behavior, transformational leadership had a a positive and significant impact on innovative work behavior, individual behavior had a positive and significant impact on employee performance, transformational leadership had a positive and significant impact on employee performance, and innovative work behavior had a positive and significant effect on employee performance.